Unravelling the Algerian Eyalet Navy’s Pivotal Contribution to the Formation of the American Naval Fleet During 1794-1816 - MOBARKI ,Salim; Guellil,Assia (Faculty of Letters and Foreign Languages Department of English, 2024)
During the Ottoman era, the Algerian Eyalet was a significant and powerful state. It had a strong navy that controlled the Mediterranean Sea and maintained diplomatic and commercial ties with many countries. This naval power helped protect its sovereignty from conflicts. In this research, we are examining key aspects such as the maritime crisis with America, the captives, and dealing with the Dey of Algiers through a peace and amity treaty, as well as tribute payments, which prompted the United States to strengthen the American Navy. The qualitative approach is used in addition to the historical research method to track the events that occurred during that period to reach the goal. This study aims to identify these historical events. Its ultimate goal is to shed light on the Algerian Eyalet’s influence over America, which prompted it to build a naval fleet. The findings reveal that America initially commended Algerian Eyalet for ensuring safe passage and agreements, including repatriate captives. In response to the threat of Barbary piracy, the United States established its Navy in 1794. The ensuing war was a reaction to Algerian dominance, which provided valuable experience for the young nation. This included promoting nationalism and unity among Americans and adopting the abolition of slavery. It also gained it a skilled political elite and a military force that protected its interests